The Influence of Organizational Culture and Work Motivation on Employee Performance - Yenni Mariani Sinurat; Christin Natalia Sianipar (Jurnal Mantik, 2021)
This study aims to determine the effect of organizational culture and work motivation on employee performance (a case study on employees of Metro Cash & Credit TebingTinggi). The results of hypothesis testing using multiple linear regression analysis with two independent variables and one dependent variable. The results showed that: The first hypothesis proposed states that: Organizational Culture has an effect on Employee Performance, from table 4.12 it is obtained that the tcount value is 13.878 with ? = 5%, t table (5%; 40-2 = 38) obtained a t-table value of 2, 02439. From this description it can be seen that tcount (13.838)>ttable (2.02439), as well as the significance value of 0.000 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the Organizational Culture Variable (X1) affects the Employee Performance Variable (Y). The second hypothesis proposed states that: Work Motivation has an effect on Employee Performance, from table 4:12 it is obtained that the t-count value is 2,150. With ? = 5%, t table (5%; 40-2 = 38) obtained t table value of 2.02439. From this description it can be seen that tcount (2.150)>ttable (2.02439), and the significance value is 0.038 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the Work Motivation Variable (X2) has an effect on the Employee Performance Variable (Y). The third hypothesis proposed states that: Organizational Culture and Work Motivation simultaneously influence employee performance. Table 4.13 shows that the Fcount value is 166.004. With ? = 5%, dk numerator: 2, dk denominator: n-k-1 (5%; 2; 37) obtained Ftable value of 3.25. From this description it can be seen that Fcount (166.004)>Ftable (3.25), and a significance value of 0.000 <0.05, it can be concluded that the third hypothesis is accepted, meaning that the Organizational Culture Variable (X1) and Work Motivation Variable (X2) have a significant effect together (simultaneously) on Employee Performance Variables (Y).